The effects of non-esterified fatty acids and β-hydroxybutyrate on the hepatic CYP2E1 in cows with clinical ketosis. Issue 1 (8th February 2019) - Peng, Zhicheng; Li, Xiaobing; Wang, Zhe; Liu, Guowen; Li, Xinwei
Abstract: Dairy cows with ketosis display severe oxidative stress as well as high blood concentrations of non-esterified fatty acids (NEFA) and β-hydroxybutyrate (BHB). Cytochrome P4502E1 (CYP2E1) plays an important role in the induction of oxidative stress. The aim of this study was to investigate CYP2E1 expression and activity in the liver of clinically ketotic cows (in vivo) and the effects of NEFA and BHB on CYP2E1 expression and activity in hepatocytes (in vitro). Dairy cows with clinical ketosis exhibited a low blood concentration of glucose but high concentrations of NEFA and BHB. Hepatic mRNA, protein expression, and activity of CYP2E1 were significantly higher in cows with clinical ketosis than in control cows. In vitro, both NEFA and BHB treatment markedly up-regulated the mRNA and protein expressions as well as activity of CYP2E1 in cow hepatocytes. Taken together, these results indicate that high levels of NEFA and BHB significantly up-regulate the expression and activity of hepatic CYP2E1, and may be influential in the induction of oxidative stress in cows with clinical ketosis.